PENGARUH DAUN LIDAH BUAYA TERHADAP PERADANGAN JARINGAN MUKOSA RONGGA MULUT (Laporan Penelitian) - Meitha Meitha; Widurini Widurini (Faculty of Dentistry, Universitas Indonesia, 2015)
One of the traditional plants that has been broadly known as the health and healing plants is Aloe vera. It is often use to treat burns, wounds, abrasions, skin disease, alopecia, and irritation. It is further more used as a hair washed to promote hair growth and as general cosmetics to improve the complexion and to smoothen the skin. The aim of the study was to examine and compare the reaction of fresh Aloe vera and distillate Aloe vera on the inflamed oral mucosa caused by hydrogen peroxide 10%. 14 rats were used in this research and divided into 4 groups: fresh Aloe vera group (4 rats), distillate Aloe vera group (4 rats), control group I (3 rats), and control group II (3 rats). All rats in each group received 9x10 minutes application of hydrogen peroxide 10% on their vestibulum mucosa for 3 dats, except rats in control group I received application of aquadest. On the 4th day, all rats in each group received 9x5 minutes with their own group's material for 3 days. The histological examination was done by scoring the density of monocytes in the inflammation area. Statistical result shows that there are differences of oral mucosa reactions between distillate Aloe group and fresh Aloe group. Fresh Aloe group shows the decrease of lymphocytes cell higher than distillate Aloe group. Based on this research , it can be concluded that application with fresh Aloe vera can cure oral mucosa inflammation caused by hydrogen peroxide 10% better than application with distillate Aloe vera.